Consequences of work-family conflict - Nohe, Christoph (2014)
Most employees are challenged to combine work and family roles. Although both roles can provide self-esteem, self-fulfillment, and happiness, they can also interfere with each other making it more difficult to fulfill work and family demands. Work–family conflict is the construct that captures interference between work and family roles. High work–family conflict has been associated with potential consequences such as low health, high turnover intentions, and low job performance. My main aim in this dissertation is to extend research on work–family conflict and potential consequences. To this end, I conducted three empirical studies. Study 1 examined the relationship between work–family conflict and strain, an umbrella term for constructs such as exhaustion, depression, and somatic symptoms. Specifically, my coauthors and I tried to work toward resolving two debates. The first debate is about the direction of relationships between work–family conflict and strain. We examined whether work–family conflict predicts strain, whether strain predicts work–family conflict, or whether work–family conflict and strain reciprocally predict each other. The second debate is about the pattern of relationships between work–family conflict and domain-specific outcomes. The currently dominant cross-domain perspective suggests that family-to-work conflict (FWC) is mainly related to work-related strain. The less-popular matching perspective, however, suggests that work-to-family conflict (WFC) is mainly related to work-related strain. To address those two debates, we applied meta-analytic path analysis to 33 panel studies (total N = 13,029) that had repeatedly measured work–family conflict and strain. For the direction of relationship, results showed reciprocal relationships for both forms of work–family conflict and strain. More specifically, WFC predicted strain (β = .08) and strain predicted WFC (β = .08). Similarly, FWC predicted strain (β = .03) and strain predicted FWC (β = .05). These findings held for both men and women and for different time lags between the two measurement waves. For the debate on matching versus cross-domain relationships, results showed that WFC had a stronger relationship with work-specific strain than did FWC, supporting the matching hypothesis. Study 2 focused on work–family conflict and turnover intentions. More specifically, it compared two theoretical perspectives that make competing predictions about the relationships between work–family conflict and domain-specific outcomes. The cross-domain perspective predicts that FWC should be more important than WFC in predicting increases in turnover intentions. The matching perspective, however, predicts that WFC should be more important than FWC in predicting increased turnover intentions. We expanded the debate about matching versus cross-domain relationships by testing whether work-family specific social support should stem from the same domain as the conflict as the matching principle would indicate or from the other domain as the cross-domain perspective would indicate. Additionally, we hypothesized that changes in WFC and FWC predict changes in turnover intentions and tested reciprocal relationships between WFC/FWC and turnover intentions. With a time-lag of five months, 665 employees from a large company filled out surveys at two time points. Results revealed that (increases in) WFC predicted increased turnover intentions, whereas (increases in) FWC did not. Work-family specific support from the leader buffered the relationship between WFC and increased turnover intentions, but work-family specific support from family and friends did not. Furthermore, results revealed reverse relationships such that turnover intentions predicted increased WFC and FWC. Taken together, the study results supported the matching principle rather than the cross-domain perspective. The reverse relationships found between work–family conflict and turnover intentions challenge the common view that work–family conflict antecedes turnover intentions unidirectionally. Study 3 examined the cross-domain relationship between work–family conflict and job performance. Overall, Study 3 was intended to better understand work–family conflict as a dynamic construct that changes over short periods, such as from day-to-day. Specifically, we used a within-person daily research paradigm to examine the relationship between daily FWC and daily job performance. On the basis of theory on dynamic behavior, we hypothesized that daily FWC impairs daily job performance through the mechanism of daily concentration. Additionally, we predicted that psychological detachment from work during time off (i.e., mentally switching off) buffers the negative relationship between daily FWC and daily job performance. Over one workweek, 95 employees from a large German company completed two surveys each day. Multilevel modeling results showed that daily FWC was negatively associated with daily job performance and that daily concentration mediated this relationship. Furthermore, general psychological detachment, but not daily psychological detachment, buffered the negative relationship between daily FWC and daily job performance. The findings of Study 3 advance our understanding of dynamic short-term processes at the intersection of work and family by demonstrating that short-term changes in FWC go along with fluctuations in job performance. This dissertation offers several practical implications. For example, Study 2 shows that work-family specific leader support buffers the relationship between high WFC and high turnover intentions. Study 3 shows that psychological detachment from work during time off buffers the relationship between high FWC and low job performance. Thus, organizations should foster leader support and encourage their employees to psychologically detach from work during time off to buffer the relationship between work–family conflict and relevant business outcomes. In sum, this dissertation contributes to research on work–family conflict and its potential consequences by addressing ongoing debates and gaps in the literature.
Zsfassung in engl. Sprache. - Enth. Zeitschriftenartikel
Keywords: Hochschulschrift; Psychologie; Konflikt; Familie; Arbeit